2018
DOI: 10.1089/mdr.2017.0397
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Colistin Resistance Among Pandrug-Resistant Isolates ofAcinetobacter baumanniiwith High Case-Fatality Rate in Intensive Care Unit Patients

Abstract: Colistin is considered a last-hope antibiotic against extensively drug-resistant isolates of Acinetobacter baumannii. Resistance to colistin has been rarely reported for A. baumannii. Genetic alterations in the PmrA-PmrB two-component system and lipid A biosynthesis genes may be associated with colistin resistance. We investigated molecular mechanisms of colistin resistance in three clinical colistin-resistant (ColR) and two colistin-susceptible (ColS) A. baumannii isolates. A ColR mutant was generated in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 24 publications
4
20
0
Order By: Relevance
“…In this study, clinical isolates of CR-ColRAB and CR-ColSAB were characterized for multiple colistin resistance mechanisms. Mutation analysis in lpxACD identified three nonsynonymous mutations; Q4K, V63I and E117K within lpxD in both CR-ColRAB and CR-ColSAB which concurs with previous studies [26,27]. Recent studies report that mutations in pmrB as the major contributor for colistin resistance in A. baumannii [24,26,28,29].The current study identified a non-synonymous mutation, A138T in pmrB while previous studies report other amino-acid substitutions together with A138T which is contrary to the current study [24,26,29].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, clinical isolates of CR-ColRAB and CR-ColSAB were characterized for multiple colistin resistance mechanisms. Mutation analysis in lpxACD identified three nonsynonymous mutations; Q4K, V63I and E117K within lpxD in both CR-ColRAB and CR-ColSAB which concurs with previous studies [26,27]. Recent studies report that mutations in pmrB as the major contributor for colistin resistance in A. baumannii [24,26,28,29].The current study identified a non-synonymous mutation, A138T in pmrB while previous studies report other amino-acid substitutions together with A138T which is contrary to the current study [24,26,29].…”
Section: Discussionsupporting
confidence: 89%
“…29,30 Scattered reports of its resistance to the last-line treatment, colistin, have raised further concerns for the medical field. 7,8,23,24 A. baumannii has different mechanisms for resistance to colistin. It is also featured by having ability to produce biofilms, which are very effective in maintaining and retaining this bacterium in hospital environments.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm-related genes (bap, ompA, csuE, and bla PER1 ) and colistin resistance-related genes (mcr-1, mcr-2, pmrA, and pmrB) were detected using PCR. [21][22][23] Bacterial DNA extraction was performed in accordance with the boiling method. 24 The PCR assay was carried out in a final volume of 25 μL containing Taq DNA polymerase (1 U; CinnaGen, Iran), dNTPs (100 μM), Taq buffer (5×), DNA template (50 ng), and forward and reverse primers (25 pM).…”
Section: Molecular Detection Of Resistance Genesmentioning
confidence: 99%
“…2016; Rapoport et al . 2016; Skov and Monnet 2016; Kluytmans 2017; Haeili, Kafshdouz and Feizabadi 2018) necessitate the development of novel alternatives. Efforts to develop polymyxin derivatives as ARBs to potentiate the actions of antibiotics have been spearheaded in recent decades by Prof. Martti Vaara and co-workers.…”
Section: Antibiotic Resistance Breakersmentioning
confidence: 99%